(untitled) (Research, Society and Development, 2020)
Not from today that essentially traditional methods and classrooms have failed to provide motivating teaching. In fact, the digital revolution caused by hyperconnection, availability, and access to information has profoundly transformed social relations, with a direct reflection on how to teach. This scenario draws attention to the need to analyse the impacts of the use of technologies in education and, thus, this paper presents an investigation carried out with 70 students of the 3rd year of high school in a private school in the City of São Paulo, where it was used Socrative application as a tool for engaging in the Physics’ learning process. After knowing the tool well, from an experiment in the school’s computer lab, students began to use it for activities outside the school environment. At the end of the school year, students evaluated the application through a survey, which highlighted the positive and negative aspects and how its use influenced the learning’s process involvement. The study disclosed that the student-application-smartphone interaction promoted better student engagement, a fact confirmed by the effective participation in the “virtual” classes held outside the traditional school environment and the answers to the applied survey. Thus, it is considered that the use of Digital Information and Communication Technologies (TDICs) is an efficient and viable alternative, which should be considered when rethinking how to teach and seek objects of the transformation of the traditional classroom into a model that encourage the student’s construction of knowledge.